INSPEÇÃO E AVALIAÇÃO DA DEGRADAÇÃO DA VIDA ÚTIL EM EDIFICAÇÕES HISTÓRICAS DE LUZIÂNIA/GO - Rocha, Victor; Melo, Carlos E. L. (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The research with the theme Inspection and Evaluation of the Degradation of Useful Life in Historic Buildings of Luziânia/GO made a bibliographical and historical review on the city of Luziânia, thus showing its historical and patrimonial importance for Brasilia, for the state of Goiás and for the country. Through data collected at IPHAN and visits to the city, it mapped intangible assets that have not yet been mischaracterized by time and by man. With this mapping it was possible to delimit a quantity of real estate to perform the inspections and evaluations of degradation of the useful life. Four properties were chosen that have historical and cultural importance for the city. Parallel to the bibliographic review, the non destructive technique of visual inspection was used to evaluate the visual characteristics in function of the presence of pathological manifestations, collecting data and photographic records of the same. With these data it was possible to perform GUT matrices to determine the degree of priority for resolution of pathologies. The research intends to contribute to the preservation of the immovable patrimonial assets of the city, with the creation of a plan of action.